Implementation of a monitoring system at the prototype level of vital signs: pulse, temperature and oxygen saturation for patients - Bejarano Reyes, Mauricio Alonso (2021)
The Internet of Things is a digital interconnection between everyday objects and the Internet, which is generally used to improve comfort in daily tasks and optimize business. Thus, it can be integrated into the health world to give it medical applications, being one of the typical application scenarios of the telemedicine service, such as remote medical care. In this way, this article describes the development of a monitoring system for vital signs: pulse, temperature, and oxygen saturation in the blood, which is based on the comparison and selection of components through the research methodology, and its validation through statistical analysis. This monitoring system seeks to be used in the care of patients with home treatments as a compact and low-cost system to provide timely medical information and implement future Cloud Computing and Internet of Things technologies to perform remote monitoring of objective and subjective patient data. In addition, the design and implementation of the mainboard, the selection of biomedical sensors, the preparation of supports and programming are detailed.